Heart Rate and Perceptual Responses to Graded Leg and Arm Ergometry in Healthy College-Aged Saudis: Effects of Gender and Exercise Mode - Salwa B. El-Sobkey; Hazzaa M. Al-Hazzaa (Journal of Novel Physiotherapy and Physical Rehabilitation - Peertechz Publications, 2014)
Objective: To assess gender differences in heart rate (HR) and perceptual responses during leg versus arm ergometry among healthy college-aged Saudis.  Methods: Forty healthy college-age Saudis (20 males) performed, in a random cross-over design, two maximal graded exercise leg (LE) and arm ergometry (AE). HR was continuously monitored/recorded during resting and throughout exercise period. Participants rated their perceived exertion (RPE), using Borg scale, at the end of each two-minute stage. Lactate from capillary blood was measured before and one minute after each test.  Results: Females had significantly (p<0.01) higher resting HR and lower resting blood pressure than males. There were significant (p<0.05) gender by exercise mode interactions in most of the parameters. Peak HR (bpm) was significantly (p<0.001) higher during LE than AE in males (181±12 vs 172±21) and females (176±9 vs 162±16), without significant gender difference. Males had significantly (p<0.015) higher values than females in absolute peak work load (WL) and exercise time and lower HR and RPE at absolute sub-maximal exercise. Peak arm/leg WL ratio was significantly (p=0.006) higher among females (54.6±12.7%) compared with males (45.1±6.9%). Gender differences in HR and RPE at 50% of peak WL were significant at LE. Conclusions: Significant hemodynamic, perceptual and performance differences existed between Saudi males and females in response to LE and AE. This has important implications to exercise testing, prescription and rehabilitation.